2013
DOI: 10.1124/jpet.112.200790
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl-Hydroxylase Inhibition Preserves Endothelial Cell Function in a Rat Model of Vascular Ischemia Reperfusion Injury

Abstract: Storage protocols of vascular grafts need further improvement against ischemia-reperfusion (IR) injury. Hypoxia elicits a variety of complex cellular responses by altering the activity of many signaling pathways, such as the oxygen-dependent prolylhyroxylase domain-containing enzyme (PHD). Reduction of PHD activity during hypoxia leads to stabilization and accumulation of hypoxia inducible factor (HIF) 1a. We examined the effects of PHD inhibiton by dimethyloxalylglycine on the vasomotor responses of isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…5 Different research groups have aimed to develop individual methods to maintain vascular function during storage. 17,24 In our laboratory, we demonstrated a maintained vascular function with new iron chelators after 24 hours of ischaemia. 19 In accordance with the literature, in the present study we also found an impaired vasodilatative capacity in aortic rings after prolonged cold storage for 24 hours followed by warm HOCl-induced reperfusion injury by using vitro measurements.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…5 Different research groups have aimed to develop individual methods to maintain vascular function during storage. 17,24 In our laboratory, we demonstrated a maintained vascular function with new iron chelators after 24 hours of ischaemia. 19 In accordance with the literature, in the present study we also found an impaired vasodilatative capacity in aortic rings after prolonged cold storage for 24 hours followed by warm HOCl-induced reperfusion injury by using vitro measurements.…”
Section: Discussionmentioning
confidence: 81%
“…To simulate the whole reperfusion process the well established method of reoxygenation and rewarming with additional HOCl incubation was applied. 16,17 After prolonged cold storage and high reperfusion levels of ROS, including other less toxic oxygen species, HOCl is released from activated leucocytes and severely impairs endothelial cells and NO production, and induces apoptosis in endothelial cells and in the vessel wall through oxidative stress. After prolonged cold storage and reperfusion, high levels of ROS severely impair endothelial cells and NO production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 cGMP immunohistochemical staining. Rehydrated sections were blocked (3% goat serum) and rabbit polyclonal anticGMP primary antibody (Abcam, Cambridge, UK) incubation was performed (1:1,000) for 2 hours at room temperature.…”
Section: Tunel Reactionmentioning
confidence: 99%